Effectiveness of Continuing Nursing Education Program on Nursing Staffs, Knowledge at Kidney Transplantation Units in Baghdad Teaching Hospitals - abas, Anmar; mohammed, widad (Iraqi National Journal of Nursing Specialties, 2013)
Objective: The study aims to determine the effectiveness of the continuing nursing education program on nursing staffs knowledge in kidney transplantation unit and to find out the relationship between nursing staffs knowledge and demographic characteristics (age, gender, education level, and years of experiences in kidney transplantation unit). Methodology: A quasiexperemental design (One-group Pretest - Posttest design) was carried out in kidney transplantation units at Baghdad Teaching Hospitals, from December 2011 to July 2012. A nonprobability (purposive sample) of (16) nurses were selected from kidney transplant units at Baghdad teaching hospitals, the choice was based on the study criteria. The data were collected through the use of constructed questionnaire and consist from two major parts, part one consist of demographic characteristics contain (9) and part two consist of (58) items of a multiple choice questions distributed in (8) major sections. Validity of the instrument was determined through a panel of (8) experts, and reliability through a pilot study. The data were analyzed through the application of descriptive and inferential statistical analysis procedures. Results: The findings of the present study indicate that the continuing nursing education program was effective on knowledge improvement of the participant’s nurses. The total percent of the improvements resulted by the effects of applying the continuing nursing education program was (43.31%). And there was a non-significant relationship between nurse’s knowledge and demographic characteristics (age, gender, education level, and years of experiences in kidney transplantation unit). Recommendation: Based on the result of the present study the researcher recommends to carrying out additional studies on application of nursing education programs about nurses practice on kidney transplantation in kidney transplant units, and nurses should be encouraged to participate in continuing education programs and training sessions about kidney transplantation.